A highly effective in vivo photothermal nanoplatform with dual imaging-guided therapy of cancer based on the charge reversal complex of dye and iron oxide. Issue 42 (22nd September 2015) - Chang, Yulei; Li, Xiaodan; Kong, Xianggui; Li, Ye; Liu, Xiaomin; Zhang, Youlin; Tu, Langping; Xue, Bin; Wu, Fei; Cao, Dianbo; Zhao, Huiying; Zhang, Hong
Abstract : A new precision treatment strategy based on the dual photothermal agent of IR-806 NIR dye and iron oxide nanocomplex was constructed for efficient image-guided in vivo photothermal therapy (PTT). Abstract : To enhance the treatment efficiency of photothermal therapy (PTT) with very little light-associated side effect, we have constructed a highly effective PTT nanoplatform for fluorescence and MRI dual imaging-guided PTT of cancer, based on IR806 dye and iron oxide complex functionalized with mPEG-PCL-G2.0PAMAM-Cit, which can be for charge-conversion for targeted accumulation in tumor. Combination of iron oxide nanoparticles and IR806 improve light to thermal conversion efficiency and lower light irradiation dose. In vitro and in vivo tests demonstrated that an effective dual imaging-guided PTT as low as 0.25 W cm −2 could be realized under a light irradiation of 808 nm. These efforts highlight the potential of this PTT nanoplatform in "precision medicine".